Analisis Pengendalian Kualitas Produk Pipa Baja Di PT Kunango Jantan Dengan Metode Six Sigma - Dzakirah Rofiana Fadri; Hary Fandeli (Jurnal Andalas: Rekayasa dan Penerapan Teknologi, 2026)
This study is motivated by the occurrence of defects in steel pipe products, which lead to decreased product quality, increased production costs, and reduced organizational competitiveness. Therefore, this research aims to evaluate the effectiveness of quality control in steel pipe production using the Six Sigma approach and to propose improvement recommendations based on the analysis results. This study adopts a quantitative approach using secondary data in the form of historical production records and defect data from 2023 to 2024. The analysis is conducted using the Six Sigma DMAIC (Define, Measure, Analyze, Improve, Control) framework. In the measurement stage, control charts, Defects per Unit (DPU), Defects per Million Opportunities (DPMO), and sigma level are calculated to assess process performance and capability. The results show that the average sigma level of the steel pipe production process is at 4 sigma, with a DPMO value of 5,355.8989, indicating that the process performance is relatively good but still requires improvement. The most dominant type of defect identified is incomplete welding. Further analysis indicates that the root causes of defects are related to human, machine, material, and method factors. Based on these findings, several improvement recommendations are proposed, including enhancing operator training, implementing routine machine maintenance, strengthening material quality control, and improving standard operating procedures (SOP). These recommendations are expected to reduce defect rates and improve overall process quality.